Tests of Burn Wound Healing with Nanogel Preparations from Ethanol Extract of Andaliman Fruit - Janice, Janice; Erwina Putri, Riri; Fioni, Fioni (Jurnal EduHealth, 2023)
Andaliman (Zanthoxylum acanthopodium DC) is a plant known for its diverse bioactive compounds, including antimicrobial and anti-inflammatory properties. Nano-gel formulations were prepared using appropriate techniques, and their physicochemical properties, including particle size, pH, viscosity, and centrifugation stability, were evaluated. Additionally, organoleptic tests were conducted to assess the sensory characteristics of the nano-gels. Furthermore, an irritation test was performed to ensure the formulation's safety when applied to the skin. The percentage of wound closure was evaluated at various time points, including days 2, 4, 6, 8, 10, 12, and 14, comparing it to a commercially available wound healing product, Bioplacenton. Initial findings showed that the nano gel formulations exhibited favorable physicochemical properties, including appropriate particle size within the nano-scale range. The pH values were within an acceptable range, and the formulations demonstrated suitable viscosity and stability during centrifugation. Organoleptic tests indicated good sensory characteristics, and the irritation test showed the formulation's safety without significant skin irritation. The percentage of wound closure increased over time for all three concentrations (F1: 5%, F2: 10%, F3: 20%). In conclusion, nano gel formulations containing various concentrations of Andaliman extract exhibited good physicochemical properties, favorable sensory characteristics, and safe application on the skin. Moreover, they demonstrated promising wound healing effects, potentially comparable to commercial wound healing agents.